2023
DOI: 10.3389/fimmu.2023.1080043
|View full text |Cite
|
Sign up to set email alerts
|

Gut and airway microbiota dysbiosis and their role in COVID-19 and long-COVID

Abstract: The gut microbiota plays a crucial role in human health and disease. Gut dysbiosis is known to be associated with increased susceptibility to respiratory diseases and modifications in the immune response and homeostasis of the lungs (the so-called gut-lung axis). Furthermore, recent studies have highlighted the possible role of dysbiosis in neurological disturbances, introducing the notion of the “gut-brain axis.” During the last 2 years, several studies have described the presence of gut dysbiosis during coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…The association of then microbiota composition with these clinical variables has been widely studied [15] and it is well described that the microbiota can modulate host immunity and physiological functions [47], Consequently, the microbiota could be key in the clinical phenotype of these patients although the specific contribution of the microbiota to the progression of the infection and a poor prognosis is not yet fully understood. This study addresses for the first time the implication of nasopharyngeal and faecal microbiota in the prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of then microbiota composition with these clinical variables has been widely studied [15] and it is well described that the microbiota can modulate host immunity and physiological functions [47], Consequently, the microbiota could be key in the clinical phenotype of these patients although the specific contribution of the microbiota to the progression of the infection and a poor prognosis is not yet fully understood. This study addresses for the first time the implication of nasopharyngeal and faecal microbiota in the prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SARS-CoV-2 infection has been extensively reported to induce dysbiosis the in the respiratory tract and the colon [17][18][19][20], characterized by increased presence of opportunistic pathogens, including Staphylococcus, Corynebacterium and Acinetobacter bacteria [14,15], which can raise the risk of secondary infections, morbidity and mortality [16]. Thus, it is evident that there is a relevant connection between the microbiome from the respiratory and gastrointestinal tracts and the development and progression of this disease, and also the recovery processes [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that gut microbiota affect lung health through an important crosstalk with the lungs, the “gut-lung axis” ( 30 ). Gut ecological dysregulation can lead to increased vulnerability to respiratory diseases ( 31 ). Gut-Lung axis is bi-directional; gut microbiota metabolites can affect the lungs through the bloodstream and it can also affect the gut microbiota when inflammation occurs in the lungs ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis may also play an important role in central inflammation through the gut–brain axis to mediate central symptoms. Because the recovery of intestinal dysbiosis requires a certain period of time, the related symptoms mediated by intestinal dysbiosis may continue to affect patients with COVID‐19 99,100 . Most patients with COVID‐19 have mild symptoms and recover well, but some patients develop severe COVID‐19.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%